Workshop Report: Implementation of the 3Rs – Regulatory Animal Testing and Current Debates on Transparency in Animal Experimentation - Nicole Lüthi; Katerina Styokova; Sara Faizee; Margot Michel (Journal of Animal Law, Ethics and One Health)
This workshop report summarizes the key findings and discussions from the event “Implementation of the 3Rs in Swiss Law – Regulatory Animal Testing and Current Debates on Transparency in Animal Experimentation”, held on March 20, 2025, in Zurich. The workshop brought together experts from academia, regulatory bodies, and NGOs to address two central topics in animal research: regulatory chemical safety assessments and transparency as a legal requirement.